Reflexive racialization and discursive affect with the #VeryAsian Hashtag. Issue 2 (4th March 2023) - Oh, David C.
ABSTRACT: On 2 January 2022, Michelle Li, a local anchor in St. Louis, played a video on Twitter of herself listening stoically to an irritated caller, who complained that Li was being 'very Asian' for mentioning that her family ate 'dumpling soup' on New Year's Day. She claimed that a White person talking about White foods would be fired. The call and Li's response resonated among Asian Americans and prompted a viral hashtag, #VeryAsian. The essay argues that users engaged in earnest accounts of their pride and lack of shame in pan-ethnic racial belonging as well as their ethnic heritage cultures. Notably, this meant eschewing memes, a common feature of Twitter discourse, and the racial humor of signifyin', a feature of Black Twitter. As a networked counter-public, the posts were affirmative articulations of pride rather than explicit anti-racist critique. Even when anger was mobilized and anti-Asian hate was named, the systems or people that produce it were abstracted, demonstrating the liminality of Asian American experience and the context collapse of Twitter.